“Make Them Stop it”: What Aboriginal Children and Youth in Australia Are Saying About Bullying - Coffin, Juli (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2011)
This paper explores and summarizes a three year research program into contextualizing bullying in an Aboriginal cultural environment for youth and children. Bullying is not a new concept; it has been passed down from one generation to the next for many years. Effects of bullying can be long term and often manifest as being the causal pathway to other undesirable behaviours. Among children and youth effects of bullying are seen in many forms, for Aboriginal children and youth these effects are magnified. Aboriginal children and youth are already over represented in truancy, juvenile detention and anti social behaviours, bullying is in the mix and it is preventable. Intra racial bullying and turning inward on one’s own cultural group is surely a cry for help with these complex and intricate relationship issues. This paper concludes by considering some of the implications of these findings for future research and conceptualization and has practical solutions for those who are in the care and position to influence the outcomes for Aboriginal communities.